2020
DOI: 10.26434/chemrxiv.13265618.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accessing Chemo- and Regioselective Benzylic and Aromatic Oxidations by Protein Engineering of an Unspecific Peroxygenase

Abstract: Unspecific peroxygenases (UPOs) enable oxyfunctionalisations of a broad substrate range with unparalleled activities. Tailoring these enzymes for chemo- and regioselective transformations represents a grand challenge due to the difficulties in their heterologous productions. Herein, we performed a protein engineering in <i>S. cerevisiae</i> with the novel <i>Mth</i>UPO. Experimental approaches were combined with computational modelling resulting in the screening of more than 5,300 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…By screening more than 5000 transformants, the catalytic efficiency on the conversion of the model substrate 5-nitro-1,3-benzodioxole (NBD) was improved 16.5-fold. Improved variants led to the chemodivergent formation of selective oxyfunctionalizations at the aromatic 37 and benzylic positions 36 , respectively, using 2-methylnaphthalene ( 35 ) as a substrate (Scheme C) …”
Section: Iron-dependent Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…By screening more than 5000 transformants, the catalytic efficiency on the conversion of the model substrate 5-nitro-1,3-benzodioxole (NBD) was improved 16.5-fold. Improved variants led to the chemodivergent formation of selective oxyfunctionalizations at the aromatic 37 and benzylic positions 36 , respectively, using 2-methylnaphthalene ( 35 ) as a substrate (Scheme C) …”
Section: Iron-dependent Enzymesmentioning
confidence: 99%
“…Improved variants led to the chemodivergent formation of selective oxyfunctionalizations at the aromatic 37 and benzylic positions 36, respectively, using 2-methylnaphthalene (35) as a substrate (Scheme 10C). 61 CglUPO from Chaetomium globosum can catalyze the epoxidation and hydroxylation of testosterone (38) yielding testosterone 4,5 β-epoxide (40) and 16α-hydroxy testosterone (39) (Scheme 10D). Those steroids exhibit crucial roles in physiological processes.…”
Section: ■ Iron-dependent Enzymesmentioning
confidence: 99%
“…To gain insights into the switch in the hydroxylation pattern observed due to the A161L mutation, we performed molecular dynamics (MD) simulations as previously shown for UPOs. 28,30 MD simulations with octane substrate bound in wild type MthUPO showed that the preferential binding conformation of octane corresponds to a buried mode that allows octane to maximise the hydrophobic interactions with multiple residues in the active site (L56, L60, F63, F154 and L206). Within this conformation, C4/ C3 and C2 are accessible to Cpd I for the homolytic hydrogen abstraction from the C-H bond (Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…13,14 Also, recent work in our laboratory addressed this issue by creating chemodivergent variants of MthUPO from Myceliophthora thermophila for benzylic or aromatic oxyfunctionalisations. 30 To harness the impressive activities of UPOs for chemo-or regioselective transformations, protein engineering approaches and directed evolution techniques are of particular interest. Directed evolution consists of random or semi-rational mutagenesis to create enzyme libraries assessed for improved enzyme abilities by high throughput analysis.…”
Section: Introductionmentioning
confidence: 99%
“…UPOs are solely relying on hydrogen peroxide as cosubstrate for the formation of the reactive oxyferryl (Compound I) intermediate. In contrast to the well-known cytochrome P450 enzymes, they do not rely on auxiliary electron transport proteins and expensive cofactors. , Recent studies demonstrate impressive activities on a wide variety of structurally diverse substrates. …”
mentioning
confidence: 99%